2011
DOI: 10.1007/s12013-011-9157-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamics of Ventricular Filling in the Embryonic Heart

Abstract: The vertebrate embryonic heart first forms as a valveless tube that pumps blood using waves of contraction. As the heart develops, the atrium and ventricle bulge out from the heart tube, and valves begin to form through the expansion of the endocardial cushions. As a result of changes in geometry, conduction velocities, and material properties of the heart wall, the fluid dynamics and resulting spatial patterns of shear stress and transmural pressure change dramatically. Recent work suggests that these transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Their simulations were performed for Reynolds numbers in the range of 1-10, corresponding to an HHstage 25 chick heart. Miller [65] also found that pressure and shear are of the same order of magnitude in a simplified two-dimensional beating heart model for Reynolds numbers on the order of 0.1. In this case, shear stress is maximized on the luminal side of the cushions, and pressure is maximized on the chamber walls during contraction.…”
Section: Shear Stress Pressure and Myocardial Activitymentioning
confidence: 88%
“…Their simulations were performed for Reynolds numbers in the range of 1-10, corresponding to an HHstage 25 chick heart. Miller [65] also found that pressure and shear are of the same order of magnitude in a simplified two-dimensional beating heart model for Reynolds numbers on the order of 0.1. In this case, shear stress is maximized on the luminal side of the cushions, and pressure is maximized on the chamber walls during contraction.…”
Section: Shear Stress Pressure and Myocardial Activitymentioning
confidence: 88%
“…However, the influence of mechanical forces and its synergy with tissue architecture in influencing cardiac valve EMT is unknown. During embryonic development, valve morphogenesis has been correlated with an increase in fluid shear stresses, mechanical strains, and altered geometry of the developing heart (19)(20)(21)(22). These observations potentially suggests interaction between mechanical forces and the factors that regulate EMT.…”
mentioning
confidence: 99%
“…Some claim that pumping of embryonic blood is induced by myocardial contractions that induce peristaltic waves (Maes et al, 2011), while others hypothesized that valveless dynamic suction is the mechanism based on observations in zebrafish and quail embryos (Forouhar et al, 2006;Jenkins et al, 2007). Consequently, numerous computational models were published in support of either of these mechanisms (Manopoulos and Tsangaris, 2005;Taber et al, 2007;Loumes et al, 2008;Avrahami and Gharib, 2008;Santhanakrishnan and Miller, 2011;Miller, 2011).…”
Section: Discussionmentioning
confidence: 99%